ELECTROMAGNETIC PERTURBATIONS OF BLACK HOLES IN GENERAL RELATIVITY COUPLED TO NONLINEAR ELECTROMAGNETIC - Jaya, Prian
Black hole is a physical object with strong gravitational interaction where no particles – even light – can escape from its force. Solution of the black hole can be obtained by general relativity – the Einstein equation –, but it mathematically yields an inevitable singularity on the metric. To avoid the singularity, we coupled the general relativity method to nonlinear electrodynamics. In the construction of regular black hole, we chose either the charge or 4-potential and Lagrangian density of the electromagnetic field. Here we obtained three new black holes: Reissner- Nordström as our linear electromagnetic couple, Maxwellian and (formula) black hole as our nonlinear electromagnetic couple. We then applied a perturbation on the black hole to compare the stability of those black holes, linear and nonlinear. A radiation will emerge from the black hole during perturbation. The radiation has form of harmonic terms with a special frequency which called quasi normal frequencies. These frequencies are in complex form. We compared the frequencies of perturbation to three black holes. In this paper we explain the basic theory of black hole and its characteristics, basic theory of linear and nonlinear electrodynamics, construction of black hole with general relativity coupled to nonlinear electrodynamics, and stability comparison between linear and nonlinear electrodynamic coupled black hole. Results of this paper are new solution of magnetic charge black hole solution and stability of perturbation in form of real and imaginary frequency of Reissner-Nordström, Maxwellian, and (formula) black hole. In general those black holes shows that magnitude of real frequencies are linearly increase while magnitude of imaginary frequencies are also linearly increase.